Ovarian expression of Insulin-Like peptide 3 (INSL3) and its receptor (RXFP2) during development of bovine antral follicles and corpora lutea and measurement of circulating INSL3 levels during synchronized estrous cycles - Satchell, Leanne; Glister, Claire; Bleach, Emma C.; Glencross, Richard G.; Bicknell, Andrew B.; Dai, Yanzhenzi; Anand-Ivell, Ravinder; Ivell, Richard; Knight, Philip G. (Endocrine Society, 2013)
Insulin-like peptide 3 (INSL3), a major product of testicular Leydig cells, is also expressed by the ovary, but its functional role remains poorly understood. Here, we quantified expression of INSL3 and its receptor RXFP2 in theca interna cell (TIC) and granulosa cell compartments of developing bovine antral follicles and in corpora lutea (CL). INSL3 and RXFP2 mRNA levels were much higher in TIC than granulosa cellandincreased progressively during follicle maturation with INSL3 peaking in large (11-18 mm) estrogen-active follicles and RXFP2 peaking in 9- to 10-mm follicles before declining in larger (11-18 mm) follicles. Expression of both INSL3 and RXFP2 in CL was much lower than in TIC. In situ hybridization and immunohistochemistry confirmed abundant expression of INSL3 mRNA and protein in TIC. These observations indicate follicular TIC rather than CL as the primary site of both INSL3 production and action, implying a predominantly autocrine/paracrine role in TIC. To corroborate the above findings, we showed that in vitro exposure of TIC to a luteinizing concentration of LH greatly attenuated expression of both INSL3 and its receptor while increasing progesterone secretion and expression of STAR and CYP11A1. Moreover, in vivo, a significant cyclic variation in plasma INSL3 was observed during synchronized estrous cycles. INSL3 and estradiol-17beta followed a similar pattern, both increasing after luteolysis, before falling sharply after the LH surge. Thus, theca-derived INSL3, likely from the dominant preovulatory follicle, is detectable in peripheral blood of cattle, and expression is down-regulated during luteinization induced by the preovulatory LH surge. Collectively, these findings underscore the likely role of INSL3 as an important intrafollicular modulator of TIC function/steroidogenesis, while raising doubts about its potential contribution to CL function.